Antimicrobial peptides: a promising strategy for lung cancer drug discovery?. (1st November 2020) - Zandsalimi, Farshid; Talaei, Sam; Noormohammad Ahari, Mehdi; Aghamiri, Shahin; Raee, Pourya; Roshanzamiri, Soheil; Yarian, Fatemeh; Bandehpour, Mojgan; Zohrab Zadeh, Zeinab
ABSTRACT: Introduction: Antimicrobial peptides (AMPs), also called host defense peptides (HDPs), are identified in almost any form of life, which play an important role in innate immune systems. They have a broad spectrum of antifungal, antiviral, antibacterial, and anticancer activities. Lung cancer remains the leading cause of global cancer-related death. Unfortunately, lung cancer chemotherapy is accompanied by serious side effects, nonspecific toxicity, and multidrug resistance. Hence, to overcome these drawbacks, anticancer peptides (ACPs) derived from AMPs may represent a potential promising synergistic treatment strategy for lung cancer. Areas covered: In this review, the authors provide the recent advancements in the use of AMPs for the treatment of lung cancer. Furthermore, the anti-lung cancer modes of action of these peptides have been fully reviewed. Importantly, various strategies for increasing the efficiency and safety of AMPs have been discussed. Expert opinion: The combination of AMPs and other cancer treatment approaches such as chemotherapy, nanoparticle-based delivery systems, and photodynamic therapy can be used as a promising revolutionary strategy for the treatment of lung cancer. The most significant limitations of this strategy that need to be focused on are low efficiency and off-target events.